Floristic composition and taxonomic structure of algae in the hyperhaline reservoirs of the northwestern Azov Sea coast (Ukraine) - Solonenko, A.M.; Bren, O.G. (M.G. Kholodny Institute of Botany, NAS of Ukraine, 2020)
The article represents the results of long-term algological studies of hyperhaline reservoirs of the northwestern coast of the Azov Sea. The features of the floristic composition and taxonomic structure of algae in aquatic (water column and bottom), aquatic-terrestrial (water’s edge, dried up water bodies, drying area) and terrestrial (elevated non-flooding areas) habitats of these objects are displayed. A specificity of the studied algoflora lies in the absence of representatives of certain characteristic phyla for the salt-water and non-saline land and water habitats of the territory of Ukraine. It was established that species composition of the studied reservoirs is depleted in comparison with other non-saline and marine ecosystems. Totally, 123 algae species were identified. They represente 7 phyla, 10 classes, 27 orders, 47 families, 68 genera. The largest number of species included three phyla: Cyanoprocaryota – 65 species (52.9% of the total number of identified species), Bacillariophyta – 26 (21.1%), Chlorophyta – 22 (17.9%). The first places among the six leading orders were taken by cyanoprocaryotes from Oscillatoriales, Nostocales, Chroococcales and diatoms from Naviculales. The most numerous species at the family level are trichomous cyanoprocaryotes from Nostocaceae, Pseudanabaenaceae, and Phormidiaceae. There were found 23 leading genera – their species richness exceeds the average indicator (1.81 species). According to the results of original studies, it was noted that all taxonomic levels of algoflora of the hyperhaline reservoirs shows features of not only saline habitats, but also of the freshwater, marine and terrestrial extreme ecosystems. Such diversity of the algal population indicates an unstable hydrological regime and complex relations of water exchange between the hyperhaline reservoirs and nearby terrestrial and aquatic habitats.